O JUAZEIRO (Zizyphus joazeiro Mart) NO CONTEXTO RURAL DO MUNICÍPIO DE VENTUROSA-PE - Juliana Cavalcanti Macedo, Darla; Ricardo Virgulino Rodrigues, Renner; Betânia Moreira Amador, Maria (Electronic Journal "Fórum Ambiental da Alta Paulista", 2013)
.